Pemanfaatan Media Pembelajaran Matematika Berbantuan Aplikasi Microsoft Mathematics : (Systematic Literature Review) - Khairunnisa Tanjung; Yahfizham Yahfizham (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
This research aims to explore the use of the Microsoft Mathematics application in mathematics learning. Using the Systematic Literature Review (SLR) method, this research summarizes the findings of four related articles. The research results show that the use of Microsoft Mathematics in mathematics learning can facilitate student understanding, simplify complex concepts, encourage independent learning, improve critical thinking skills, and assist in problem solving. The implication of this research is that the use of Microsoft Mathematics in mathematics education can provide significant benefits for student learning outcomes